2016
DOI: 10.1080/14767058.2016.1261281
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors for pneumothorax and morbidity and mortality in very low birth weight infants

Abstract: Pneumothorax in VLBW seems to be related to perinatal inflammation and surfactant administration, and it is significantly associated with a reduction in the probabilities of survival without MBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…Apiliogullari et al reported that aggregate mortality was as high as 30% in PTX patients while survivors also had an increased rate of bronchopulmonary dysplasia (4.28x vs. controls) 9 . Therefore, early and accurate diagnosis followed by adequate treatment is imperative 3,4,5,6,7,8,9,10,11,12,13,14 . Lately, less expensive US imaging systems have become readily available, and non-ionizing, fast, and repeatable LUS represents an ideal tool for the diagnosis of neonatal PTX.…”
Section: Introductionmentioning
confidence: 99%
“…Apiliogullari et al reported that aggregate mortality was as high as 30% in PTX patients while survivors also had an increased rate of bronchopulmonary dysplasia (4.28x vs. controls) 9 . Therefore, early and accurate diagnosis followed by adequate treatment is imperative 3,4,5,6,7,8,9,10,11,12,13,14 . Lately, less expensive US imaging systems have become readily available, and non-ionizing, fast, and repeatable LUS represents an ideal tool for the diagnosis of neonatal PTX.…”
Section: Introductionmentioning
confidence: 99%
“…No prior studies have identified an association between neonatal pneumothorax and the development of DWMA. However, several studies in preterm infants have identified an association between pneumothorax and an increased risk of severe IVH [44][45][46] . In a cohort of 803 very low birth weight infants, pneumothorax was significantly associated with lower odds of survival without severe IVH and/or PVL 46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies in preterm infants have identified an association between pneumothorax and an increased risk of severe IVH [44][45][46] . In a cohort of 803 very low birth weight infants, pneumothorax was significantly associated with lower odds of survival without severe IVH and/or PVL 46 . While the link between severe IVH on ultrasound and neurodevelopmental deficits is well-established, one large cohort study of 1749 extremely low birth weight infants with normal head ultrasound also identified an independent relationship between pneumothorax and cerebral palsy, suggesting other mechanisms by which pneumothorax adversely affects neurodevelopment 47 .…”
Section: Discussionmentioning
confidence: 99%
“…At the canalicular stage of lung development it is important to avoid shear force injury from volutrauma, since the incidence of pneumothorax and pulmonary interstitial emphysema (PIE) have an inverse association with gestational age [10,11]. First intention HFJV provides a lung protective strategy, which when combined with ANS, increases the potential for safer ventilation.…”
Section: Clinical Application Of Developmental Physiologymentioning
confidence: 99%